Complex probiotics alleviate ampicillin-induced antibiotic-associated diarrhea in mice - Li, Wenwen; Zhang, Siyu; Wang, Yanyan; Bian, Hongsheng; Yu, Shuang; Huang, Lili; Ma, Weiwei (Frontiers in Microbiology, 2023)
Antibiotic-associated diarrhea (AAD) is a common side effect during antibiotic treatment, which can cause dysbacteriosis of the gut microbiota. Previous studies have shown beneficial effects in AAD treatment with Bifidobacterium lactis XLTG11, Lactobacillus casei Zhang, Lactobacillus plantarum CCFM8661, and Lactobacillus rhamnosus Probio-M9. However, no studies have been conducted on the immunomodulatory effects and protective intestinal barrier function of four complex probiotics. The aim of our study is to investigate the alleviation effects of complex probiotics on ampicillin-induced AAD. BALB/c mice were randomly divided into: normal control group (NC), model control group (MC), positive drug control group (PDC), low-, medium-, and high-dose probiotics groups (LD, MD, HD). An AAD model was established by intragastric administration of ampicillin, by gavage of different doses of complex probiotics and Bifico. The weight gain, fecal water content, loose stool grade, intestinal permeability, total protein, albumin levels, intestinal barrier, cytokine levels, and gut microbiota were determined. The results showed that complex probiotics decreased the fecal water content, loose stool grade, intestinal permeability, and ileum tissue damage. Their application increased the weight gain, SIgA, TP, and ALB levels. Additionally, complex probiotics significantly decreased the levels of pro-inflammatory cytokines and increased those of anti-inflammatory cytokines. Meanwhile, the mRNA expression levels of ZO-1, occludin, claudin-1, and MUC2 were significantly upregulated in the probiotic-treated group. Furthermore, the complex probiotics increased the gut microbiota diversity and modulated the changes in the gut microbiota composition caused by ampicillin. At the phylum level, the abundance of Proteobacteria in the HD group was lower than that in the MC group, whereas that of Bacteroidetes was higher. At the genus level, the abundances of Klebsiella and Parabacteroides in the HD group were lower, whereas those of Bacteroides, Muribaculaceae, and Lactobacillus were higher than those in the MC group. Moreover, Spearman’s correlation analysis also found that several specific gut microbiota were significantly correlated with AAD-related indicators. We found that complex probiotics improved the diarrhea-related indexes, regulated gut microbiota composition and diversity, increased the expression levels of intestinal protective barrier-related genes, preserved the intestinal barrier function, and relieved inflammation and intestinal injury, thereby effectively improving AAD-associated symptoms.